Combined effect of cover crops and bio-fertilizer on sustainable popcorn maize production - Dragičević, Vesna; Simić, Milena; Dolijanović, Željko; Đorđević, Snežana; Stoiljković, Milovan; Dimkić, Ivica; Brankov, Milan (Frontiers in Plant Science, 2024)
Cover crops play an important role in low-input cropping systems with low agrochemicals inputs, based onincreasing the use of the agroecosystem services. Due to the lack of information about the impact of cover crops and bio-fertilizers on popcorn maize (Zea mays everta Sturt.) growth and yield quality, especially the popping volume and nutritive quality, such as concentration of protein and mineral elements, this research could provide essential information. Additional novelty presents The interrelation between popcorn maize productivity and quality with important groups of soil microorganisms presents additional novelty. The results demonstrated that field pea is a beneficial cover crop, especially when combined with a bio-fertilizer, supporting accumulation of maize biomass, chlorophyll, yield potential, and the concentration of protein, Ca, Mg, Fe, and Zn. Even What is more, field pea residues promoted N-fixing bacteria, and the number of total microorganisms, especially actinomycetes and decomposing bacteria, which could promote nutrient uptake and grain quality. Residues of cover crop mixtures: common vetch + winter oats and field pea + winter oats promoted the total number of microorganisms in the soil and up to the end of vegetation, a greater number of decomposition and ammonification microorganisms were found, especially when the bio-fertilizer was applied, which consequently could support a greater maize biomass. Popping volume, as a main trait of popcorn maize had the highest value in the common vetch + winter oats variant, supporting again, the statement that quality traits could be enhanced in sustainable production. Unlike living cover crops, mulch mainly affected soil microbial communities and promoted the development of actinomycetes, and cellulolytic microorganisms during the growing season. The results from this research could contribute to the development of sustainable popcorn maize production, toward improved grain quality. They could also serve as a basis for isolating beneficial soil microorganisms to develop new bio-fertilizers that could improve maize production in synergy with cover crops.